Optimizing energy efficiency over energy-harvesting LTE cellular networks - Mahdavi-Doost, Hajar; Prasad, Narayan; Rangarajan, Sampath (Proceedings / IEEE International Symposium on Information Theory, 2016)
We consider the problem of downlink scheduling in an LTE network powered by energy harvesting devices. We formulate optimization problems that seek to optimize two popular energy efficiency metrics subject to mandatory LTE network constraints along with energy harvesting causality constraints. We identify a key sub-problem pertaining to maximizing the weighted sum rate that is common for both optimization problems, and is also of independent interest. We show that the latter sub-problem can be reformulated as a constrained submodular set function maximization problem. This enables us to design constant-factor approximation algorithms for maximizing the weighted sum rate as well as the two energy efficiency metrics over an energy harvesting LTE downlink. Our proposed algorithms are simple to implement and offer superior performance.